Preliminary study on fabrication, characterization and synergistic anti-lung cancer effects of self-assembled micelles of covalently conjugated celastrol-polyethylene glycol-ginsenoside Rh2 - Peng Li; XiaoYue Zhou; Ding Qu; Mengfei Guo; Chenyi Fan; Tong Zhou; Yang Ling (Taylor & Francis Group, 2017)
The aim of this study was to develop an amphipathic polyethylene glycol (PEG) derivative that was bi-terminally modified with celastrol and ginsenoside Rh2 (Celastrol-PEG-G Rh2). Such derivative was capable of forming novel, celastrol-loaded polymeric micelles (CG-M) for endo/lysosomal delivery and thereby synergistic treatment of lung cancer. Celastrol-PEG-G Rh2 with a yield of 55.6% was first synthesized and characterized. Its critical micellar concentration was 1 × 10−5 M, determined by pyrene entrapment method. CG-M had a small particle size of 121.53 ± 2.35 nm, a narrow polydispersity index of 0.214 ± 0.001 and a moderately negative zeta potential of -23.14 ± 3.15 mV. Celastrol and G Rh2 were rapidly released from CG-M under acidic and enzymatic conditions, but slowly released in normal physiological environments. In cellular studies, the internalization of celastrol and G Rh2 by human non-small cell lung cancer (A549) cells treated with CG-M was 5.8-fold and 1.8-fold higher than that of non-micelle control. Combinational therapy of celastrol and G Rh2 using CG-M exhibited synergistic anticancer activities in cell apoptosis and proliferation assays via rapid drug release within endo/lysosomes. Most importantly, the celastrol in CG-M exhibited a long elimination half-life of 445.3 ± 43.5 min and an improved area under the curve of 645060.8 ± 63640.7 ng/mL/h, that were 1.03-fold and 2.44-fold greater than those of non-micelle control, respectively. These findings suggest that CG-M is a promising vector for precisely releasing anticancer drugs within the tumor cells, and thereby exerts an improved synergistic anti-lung cancer effect.